2008
DOI: 10.1016/j.jdeveco.2007.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Deforestation and the real exchange rate

Abstract: Deforestation is a phenomenon that has largely been concentrated in the developing world. We construct a theoretical model of deforestation that focuses on the factors affecting the incentives to transform forested land into agricultural land. We show that: (i) lower discount rates and stronger institutions decrease deforestation; (ii) a depreciation in the real exchange rate increases deforestation in developing countries whereas the opposite obtains in developed countries; (iii) paradoxically, better institu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
69
0
5

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(76 citation statements)
references
References 17 publications
2
69
0
5
Order By: Relevance
“…Furthermore, Frankel and Rose (2005) also find the EKC relationship using two-stage least squares. However, it is notable that Van and Azomahou (2007) and Arcand et al (2008) do not find support for the EKC relationship, using more improved estimation techniques than did early studies. Van and Azomahou (2007) employ not only fixed effects estimation but also semi-parametric estimation, which is more flexible than popular parametric functional forms.…”
Section: Economic Growthmentioning
confidence: 84%
See 1 more Smart Citation
“…Furthermore, Frankel and Rose (2005) also find the EKC relationship using two-stage least squares. However, it is notable that Van and Azomahou (2007) and Arcand et al (2008) do not find support for the EKC relationship, using more improved estimation techniques than did early studies. Van and Azomahou (2007) employ not only fixed effects estimation but also semi-parametric estimation, which is more flexible than popular parametric functional forms.…”
Section: Economic Growthmentioning
confidence: 84%
“…5 However, it is notable that although Arcand et al (2008) find statistically significant results in the fixed effects and their preferred specification, given by the common factor representation, they find no 4 Van and Azomahou (2007) find a statistically significant coefficient for population density, but the sign is negative, and hence it is difficult to interpret. 5 Exceptions are the results obtained for Asia in Cropper and Griffiths (1994) and the results presented in Frankel and Rose (2005).…”
Section: Political Institutionmentioning
confidence: 97%
“…We investigated the potential effect of the domestic economy on deforestation because previous analyses have either shown or suggested that (a) deforestation should decrease with increasing levels of economic development Ewers 2006); (b) high levels of inflation can lead to high discount rates that promote short-term resource exploitation (Fearnside 1997(Fearnside , 2005Laurance 1999); (c) depreciation of exchange rates can increase deforestation rates in developing countries (Arcand et al 2008) and exchange rates alter the relative value of export commodities such as soy and cattle (Kaimowitz et al 2004); (d) credit availability in the form of government subsidies underpins much of the expansion of cattle ranching across the Brazilian Amazon (Barreto et al 2006a); and (e) the need to service international debts can result in elevated rates of natural resource use and forest conversion to agriculture to facilitate economic growth (Kahn & McDonald 1995;Marquart-Pyatt 2004).…”
Section: Methodsmentioning
confidence: 99%
“…Other studies have highlighted the role played by macroeconomic -fiscal, exchange rate and / or sectoral policies -in the deforestation process (e.g. Anderson, 1990;Arcand et al, 2007). In studies dedicated to tropical deforestation, institutional factors have received special attention.…”
mentioning
confidence: 99%